Sire evaluation (single and multi-trait) in terms of relative eficiency, error variance and spearman’s coeficient of rank correlation and product moment correlation in Red Sindhi cattle - P K Mallick; A K Ghosh; Harpal Singh (Journal of Livestock Biodiversity, 2025)
The sire evaluation method, which estimated the breeding values of sires with the least error variance, was taken as the best and most efficient method. The records of production and reproduction performances of first lactation traits of 717 Red Sindhi cows, progeny of 58 sires, spread over a period of 40 years (1966-2005) from CCBF, Chiplima, Orissa under the control of Department of Animal Husbandry, Dairying and Fisheries, Ministry of Agriculture, Government of India and CBF, Kalsi, Dehradun, Uttarakhand were analyzed. The present investigation to know the eﬀectiveness and efficiency of diﬀerent sire evaluation methods was evaluated on the basis of efficiency of a particular method within sire variance or error variance, Spearman’s coefficient of rank correlations and simple correlation /product moment correlation. Most efficient methods of sire evaluation D, LSM, DFREML-I, DFREML-II, DFREML-III, BLUP-I, BLUP-II and BLUP-III in terms of relative efficiency for (single and multi-trait) were 9.70, 83.33, 100.00, 80.54, 85.17, 96.88, 96.88 and 96.03 and ranked VII, VI, I, V, IV, II, II and III respectively. Spearman’s coefficient of rank correlation among breeding values of sires’ for all eight methods ranged from 0.80 ( and DFREML-II) to1.00 (LSM with DFREML-III, BLUP-I, BLUP-II) which were positive and highly significant (P≤0.01). The rank correlations of DFREML-I (most efficient method) with , LSM, DFREML-II, DFREML-III, BLUP-I, BLUP-II and BLUP-III were 0.87, 0.99, 0.98, 0.99, 0.99, 0.99 and 0.96, respectively and were highly significant (P≤0.01). The high and significant rank correlations between the breeding values of common sires estimated by diﬀerent methods indicated that all these methods did not diﬀer significantly in ranking of sires. The high relative efficiency of BLUP-I and BLUP-II (both 96.88 percent) in comparison to most efficient method along with high product moment correlation of BLUPF90-I and BLUPF90-II with DFREML-I indicated that either of these two methods could possibly be used for evaluation and ranking of Red Sindhi sires with equal efficiency and accuracy.